(untitled) (International Journal of Biology and Chemistry, 2020)
A new approach to the analysis of the processes that led to the appearance of Life on Earth was proposed. The approach is based on the idea of the evolution of the Earth’s shells as a system whole, which corresponds to the interpretation of the concept of “complex system” based on the analogy with neural networks. This analogy allows us to show that there are evolutionary mechanisms for which the primary one is the evolution of an analog of a neural network that is complementary to a specific complex system. The transformation of the system in this case takes place at the level of restructuring its structure, which at the next stage of evolution creates prerequisites for the “selection” of elements that correspond to the new state of the system as a whole. Experimental evidence of the validity of this approach for the interpretation of the origin of Life has been obtained based on the analysis of the formation of a comparative new class of macromolecular systems – hydrophilic interpolymer associates. It was shown that a solution of two interacting polymers, in which hydrophilic interpolymer associates are formed, is a direct analog of a neural network in a defined range of conditions. This object is capable of evolving as a whole, which proves the possibility of implementing an alternative mechanism of evolution considered in the framework of Darwinian theories.